Screening approaches and potential of isolated lactic acid bacteria for improving fermentation of Saccharina latissima - Evangelia Zioga; Susan Løvstad Holdt; Fredrik Gröndahl; Claus Heiner Bang-Berthelsen (BMC Biotechnology)
Abstract Background With the growing interest in applying fermentation to seaweed biomasses, there is a need for fast and efficient selection of microbial strains that have the ability to 1) acidify quickly, 2) utilize seaweed constituents and c) exhibit some proteolytic activity. The present study aims to provide a fast methodology to screen large bacterial collections for potential applications in optimized seaweed fermentations, as well as investigate and assess the performance of a selected bacterial collection of the National Food Institute Culture Collection (NFICC) in seaweed fermentation. This approach is directed toward high-throughput (HT) methodologies, employing microwell assays for different phenotypical characteristics of lactic acid bacteria isolated from different sources. The overarching aim is the deeper understanding of the selection criteria when designing starter cultures for seaweed fermentation. Results By employing high-throughput analytical workflows, the screening processing time is minimized, and among the different strains from a well-characterized strain collection, it was possible to distinguish between strong acidifiers and to replicate similar results when the volumes were scaled from 96-well plates to lab-scale fermentations (40 mL) of whole seaweed. Lactiplantibacillus plantarum, Lacticaseibacillus paracasei and, to a lesser extent, Lacticaseibacillus rhamnosus were among the fastest strains to reach the lowest endpoint pH values (< 4.5) in less than 48 h. Although the results regarding proteolytic capacity were not sufficient to prove that the candidates can also provide some flavor generation by the cleavage of proteins, NFICC1746 and NFICC2041 exhibited potential in releasing free alanine, glutamate and asparate as free amino acids. Conclusions With the described methodology, a large number of terrestrial lactic acid bacteria (LAB) isolates were screened for their performance and possible application for fermentation of brown sewaeeds. With a a fast conversion of sugars to organic acids, three potential new plant-isolated strains from NFICC, specifically Lactiplantibacillus plantarum ssp. argentoratensis (NFICC983), Lacticaseibacillus paracasei (NFICC1746) and Lacticaseibacillus rhamnosus (NFICC2041), were identified as promising candidates for future synthetic consortia aimed at application in bioprocessed seaweed. The combination of such strains will be the future focus to further optimize robust seaweed fermentations.